An Analysis of Lexical Neologisms on Coronavirus Disease 2019 Pandemic to Enhance Morphological Knowledge - Alni Sidqiyah Afrika; Kheryadi Kheryadi; Siti Sa'diah; Afif Suaidi (Journal of English Language Teaching and Linguistics, 2021)
The aim of this study is to find neologisms formed during the coronavirus disease 2019 (COVID-19) pandemic, as well as to categorize the content terms and describe the neologisms' word-formation processes. The qualitative method was used in this study, which was based on a content analysis approach. The focus of this study was on online articles and news portal websites that focused on the lexical problem of language used in the production of neologisms, with the goal of enriching the understanding of neologism as a study of analytical issue during the coronavirus pandemic. It was gathered using document reading and note-taking approaches. In addition, the referential identity technique was employed to examine the data in this study. The findings of this study demonstrate that 28 neologisms were discovered during the research process. There are three types of content words that have been discovered: nouns, verbs, and adjectives. Borrowing, derivation, compounding, clipping, blending, coinage, and multiple processes are among the seven categories of word-formation processes identified in this study. Finally, it can draw some meaningful results about the use of morphology learning strategies to engage the teaching and learning process so that learners can consistently achieve learning objectives.